2021
DOI: 10.3390/ijms22031231
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Disruption Increases Amyloid-Related Pathology in TgSwDI Mice

Abstract: In Alzheimer’s disease (AD), several studies have reported blood-brain barrier (BBB) breakdown with compromised function. P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are transport proteins localized at the BBB luminal membrane and play an important role in the clearance of amyloid-β (Aβ). The purpose of this study was to investigate the effect of pharmacological inhibition of Aβ efflux transporters on BBB function and Aβ accumulation and related pathology. Recently, we have developed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
1
12
1
Order By: Relevance
“…4), and suggested NF-κB pathway as a potential mechanism for BBB disruption. Data from the in vivo studies showed downregulation of P-gp and BCRP, and upregulation of the receptor for advanced glycation end products (RAGE), which accompanied activation of NF-κB pathway in mouse brains (40). Our study has confirmed that elacridar impairs P-gp and BCRP levels.…”
Section: Discussionsupporting
confidence: 71%
“…4), and suggested NF-κB pathway as a potential mechanism for BBB disruption. Data from the in vivo studies showed downregulation of P-gp and BCRP, and upregulation of the receptor for advanced glycation end products (RAGE), which accompanied activation of NF-κB pathway in mouse brains (40). Our study has confirmed that elacridar impairs P-gp and BCRP levels.…”
Section: Discussionsupporting
confidence: 71%
“…To prevent Aβ deposition and circumvent the toxic effects, various Aβ-scavenger pathways work together in the brain, including BBB transportation, extracellular degradation by Aβ-proteolytic enzymes, cellular uptake, intracellular degradation, interstitial fluid (ISF) bulk flow, and CSF absorption ( Ma et al, 2018 ; Abdallah et al, 2021 ). Studies have shown that 50% of Aβ is transported into the blood across the BBB by LRP-mediated transcytosis and degradation of Aβ in vascular smooth-muscle cells ( Tanzi et al, 2004 ).…”
Section: Amyloid-βmentioning
confidence: 99%
“…The Aβ42-mediated reduction of P-gp has been linked to NF-κB-signaling in the murine bEnd.3 cell model [ 63 ]. Changes in NF-κB-signaling have also been observed when treating TgSwDI mice with the dual-transporter inhibitor elacridar (BCRP and P-gp inhibitor) to reduce BBB efflux capacity, leading to a further increase in hippocampal Aβ-load and a reduction in P-gp abundance [ 64 ]. For Aβ40 treatments, changes in P-gp protein amount were linked to the transporter’s ubiquitination mediated by NEDD4-1, which, due to proteosomal degradation, reduces P-gp surface density [ 65 , 66 , 67 ].…”
Section: Transporter Regulationmentioning
confidence: 99%